2011
DOI: 10.12659/msm.881702
|View full text |Cite
|
Sign up to set email alerts
|

Conservative treatment of an aortoesophagial fistula after endovascular stent grafting for a thoracic aortic aneurysm: Case report

Abstract: SummaryBackgroundAortoesophageal fistula (AEF) is an uncommon condition that presents a problem in therapy because of the high rate of morbidity and mortality associated with its surgical management and the uniformly fatal outcome of medical treatment. In this article we describe a case of secondary AEF after endoluminal stent grafting of the thoracic aorta, which was observed by only conservative management and followed up for 14 months with no signs of recurrent hemorrhage or chronic mediastinitis.Case Repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…Generally, conservative management is the mainstay of treatment of secondary AEF after TEVAR as most of these patients have contraindications to major surgery given their poor general condition [4, 69]. Conservative management includes the use of broad-spectrum antibiotics, medical blockade of gastric acid with a proton-pump inhibitor, and enteral feeding via percutaneous endoscopic gastrostomy (PEG) to protect the esophageal lesion [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, conservative management is the mainstay of treatment of secondary AEF after TEVAR as most of these patients have contraindications to major surgery given their poor general condition [4, 69]. Conservative management includes the use of broad-spectrum antibiotics, medical blockade of gastric acid with a proton-pump inhibitor, and enteral feeding via percutaneous endoscopic gastrostomy (PEG) to protect the esophageal lesion [1].…”
Section: Discussionmentioning
confidence: 99%
“…Secondary aortoesophageal fistula (AEF) after thoracic endovascular aortic repair (TEVAR) is relatively rare [16], with a reported incidence of 1.7% to 1.9% [4, 7]. Treatment options are very limited, as these patients are usually not candidates for open surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Las secundarias son infrecuentes y son causadas como complicación de una cirugía aórti-ca 7 . En los últimos años ha aumentado el número de reportes de FAE, debido al aumento en el uso de endoprótesis esofágicas para aliviar la disfagia por cáncer y el desarrollo de la terapia endovascular de aneurismas de aorta torácica [8][9][10][11] . Por último, la RT en forma independiente (no asociada a tratamiento de cáncer de esófago) también ha demostrado ser causante de fistulización 12 .…”
Section: Discussionunclassified
“…Some patients whose conditions made them unlikely to tolerate surgical intervention were reported to survive with conservative treatment, consisting of anti-biotic therapy and percutaneous drainage/ aspiration with/without TEVAR, during a limited period, when they had only a small fistula with a small amount of fluid collection around the fistula, and with no evidence of sepsis [31,42]. Kasai et al reported a case of post-TEVAR AEF with advanced hepatocellular carcinoma that survived after conservative management alone without TEVAR for 14 months after the initial bleeding event [76]. Numan et al described a case of post-TEVAR AEF related to an infected aneurysm that was treated by CT-guided insertion of a drainage catheter [77].…”
Section: Palliative Treatment For Aefmentioning
confidence: 99%